Cadmium exposure is associated with testosterone levels in men: A cross-sectional study from the China National Human Biomonitoring. (November 2022) - Qiu, Yidan; Lv, Yuebin; Zhang, Miao; Ji, Saisai; Wu, Bing; Zhao, Feng; Qu, Yingli; Sun, Qi; Guo, Yanbo; Zhu, Yuanduo; Lin, Xiao; Zheng, Xulin; et al.
Abstract: Background: Sex hormone disorders can cause adverse health consequences. While experimental data suggests that cadmium (Cd) disrupts the endocrine system, little is known about the link between Cd exposure and sex hormones in men. Methods: We measured blood cadmium (B-Cd), urine cadmium (U-Cd), serum testosterone and serum estradiol in men aged ≥18 years old participating in the China National Human Biomonitoring program, from 2017 to 2018. Urine cadmium adjusted for creatinine (Ucr-Cd) and the serum testosterone to serum estradiol ratio (T/E2 ) were calculated. The association of Cd exposure to serum testosterone and T/E2 in men was analyzed with multiple linear regression models. Results: Among Chinese men ≥18 years old, the weighted geometric mean (95% CI) of B-Cd and Ucr-Cd levels were 1.23 (1.12-1.35) μg/L and 0.53 (0.47-0.59) μg/g, respectively. The geometric means (95% CI) of serum testosterone and T/E2 were 18.56 (17.92-19.22) nmol/L and 143.86 (137.24-150.80). After adjusting for all covariates, each doubling of B-Cd level was associated with a 5.04% increase in serum testosterone levels (β = 0.071; 95%CI: 0.057-0.086) and a 4.03% increase in T/E2 (β = 0.057; 95%CI: 0.040-0.075); similar findings were found in Ucr-Cd. Conclusions: In Chinese men, Cd may be an endocrine disruptor, which is positively associated with serum testosterone and T/E2 . Graphical abstract: Image 1 Highlights: Cadmium exposure was positively associated with testosterone in Chinese men. Cadmium exposure was positively associated with T/E2 in Chinese men. Cadmium can act as an endocrine disruptor to affect hormone homeostasis in men.